Service Delivery and Financial Management in a New Province : Gorontalo Public Expenditure Analysis 2008 - World Bank (Washington, DC, 2012)
As one of Indonesia's recently established provinces, 2001 Gorontalo has faced numerous challenges, the most daunting being one of the country's highest levels of poverty. Gorontalo's sub-national governments shoulder a heavy responsibility in ensuring the rapid development of the region, alleviating poverty and improving the provision of basic public services especially in education and health and making sure those services reach the poorest and most vulnerable groups. In performing these crucial tasks, the success of sub-national governments depends to a large degree on three factors: the ability of sub-national governments to define and then translate their visions for development into effective development plans; the existing capacity of the government bureaucracy; and the availability of budgetary resources. A clear and well-articulated vision is needed to guide regional development, one that should serve to synergize the efforts of multiple stakeholders to make full use of the latent potential that exists in Gorontalo. Moreover, for a region with limited resources such as Gorontalo, strong leadership is needed to encourage the people to make the best possible use of those resources in providing a better future to all levels of society. This report can benefit the provincial and district governments of Gorontalo, as well as other regional governments, in serving as a reference tool for reform efforts in regional public financial management and regional development planning. Ultimately, this report can contribute towards better management of regional public finances and government bureaucracy, leading to new standards in effective entrepreneurial government.